Impact of atropine on changes in choroidal thickness in children with myopia: a meta-analysis of randomized controlled trials - Liu, Li Ping; Tang, Yun; Zhang, Jun Na; Du, Chi Xin (Frontiers in Medicine, 2025)
IntroductionAtropine is used to treat myopia, and choroidal thickness (ChT) has been suggested as a biomarker for treatment response. However, randomized controlled trials (RCTs) have reported inconsistent results regarding their efficacy. This study aimed to assess the effect of atropine on ChT in children with myopia.MethodsA systematic review and meta-analysis of RCTs was conducted using PubMed, Cochrane, Embase, and Web of Science databases, including trials registered online, from inception to March 2025. Eligible studies were those that involved patients aged <18 years with myopia treated using atropine sulfate eye drops and reported ChT outcomes. Meta-regression and the Cochrane I2 test were used to assess heterogeneity, respectively. Publication bias was evaluated using Funnel plots and Egger’s and Begg’s tests. Sensitivity analysis was used to examine the impact of individual studies.ResultsOverall, 11 RCTs involving 1,784 eyes of children with myopia were included. Four doses of atropine (0.01, 0.025, 0.05, and 0.1%) were administered. Subfoveal ChT (SFChT) significantly thickened in the atropine group compared with the control group (placebo or spectacles) during the trial periods [weighted mean difference (WMD): 11.83 μm, 95% confidence interval (CI): 0.88–22.79 μm, I2 = 98.8%, p = 0.000]. Additionally, 0.01% atropine showed the best effect in ChT changes at superior 1 and inferior 1 compared with control. Notably, 0.05% atropine demonstrated the most significantly thickened SFChT (WMD: 25.70 μm, 95% CI: 17.46–33.94 μm), had the best spherical equivalent control (WMD: 0.54 D, 95% CI: 0.38–0.70 D), and had the least axial length elongation (WMD: −0.21 mm, 95% CI: −0.28 to 0.14 mm).ConclusionThe results showed that atropine may increase ChT than control. Notably, 0.05% atropine may demonstrate the most favorable outcomes for ChT, spherical equivalent, and axial length.Systematic Review Registrationhttps://inplasy.com/?s=INPLASY202320027.